Self-representation: women's stories and feminist stories - Guimarães, Marta Mencarini (2021)
This article proposes reflections on the self-representation of women artists in the exhibitions Women’s Stories: artists until 1900 and Feminist Stories: artists after 2000, exhibitions that took place at the São Paulo Art Museum Assis Chateaubriand (Masp), 2019. The investigation is based on two distinct experiences: the visit to the Museum and the relations established with the texts published in the exibition’s catalogue and anthology, in dialogical constructions between theoreticians Ana Paula Cavalcanti Simioni, Linda Nochlin and Michelle Perrot. Through the research, it was possible to establish the importance of the self-representation as an axiomatic resource which exposes gender conflicts existing in the Arts context, as well as its transforming force which is expressed politically and creates other ways for the agent to show themselves in the word.